2019
DOI: 10.1002/mame.201900326
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol)–Carbon Nanodots Fluorescent Hydrogel with Superior Mechanical Properties and Sensitive to Detection of Iron(III) Ions

Abstract: A high‐strength fluorescent hydrogel is prepared by physical cross‐linking of carbon nanodots (CNDs) with poly(vinyl alcohol) (PVA). The stretching and compression of the PVA hydrogel are improved with CNDs by 176% and 64%, respectively. It still has excellent self‐healing behaviors without adding other healing agents. In addition, the search for rapid detection of heavy metals is still a huge challenge. The resulting hydrogel exhibits fluorescence quenching in the presence of Fe3+ by the fluorescence characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Designing scaffolds with suitable mechanical properties is an essential criterion in tissue engineering applications as the cell adhesion, proliferation, and differentiation are highly dependent on the mechanical property of the scaffold [ 25 , 102 ]. Scientific studies have reported that the scaffold materials, including fiber, film, and hydrogel, exhibited substantially increased mechanical properties due to the presence of CDs [ 103 , 104 , 105 , 106 , 107 ]. For example, Ghorghi et al revealed that the incorporation of CQDs into the polycaprolactone- captopril (PCL-CP) scaffold led to an enhanced tensile strength (22.09 ± 0.06 MPa) and Young’s modulus (2.83 ± 0.23 MPa) than that of pure PCL scaffold (tensile strength 6.86 MPa and Young’s modulus 0.15 MPa).…”
Section: Properties Of Carbon Dotsmentioning
confidence: 99%
“…Designing scaffolds with suitable mechanical properties is an essential criterion in tissue engineering applications as the cell adhesion, proliferation, and differentiation are highly dependent on the mechanical property of the scaffold [ 25 , 102 ]. Scientific studies have reported that the scaffold materials, including fiber, film, and hydrogel, exhibited substantially increased mechanical properties due to the presence of CDs [ 103 , 104 , 105 , 106 , 107 ]. For example, Ghorghi et al revealed that the incorporation of CQDs into the polycaprolactone- captopril (PCL-CP) scaffold led to an enhanced tensile strength (22.09 ± 0.06 MPa) and Young’s modulus (2.83 ± 0.23 MPa) than that of pure PCL scaffold (tensile strength 6.86 MPa and Young’s modulus 0.15 MPa).…”
Section: Properties Of Carbon Dotsmentioning
confidence: 99%
“…In a recent example, Wang and co-workers developed a fluorescent poly­(vinyl alcohol) (PVA) hydrogel containing carbon nanodots (CNDs) synthesized from m -phenylene­diamine and methacrylic acid for Fe 3+ sensing . While the CNDs alone could emit fluorescence, encapsulation in PVA improved their photostability.…”
Section: Hydrogel Molecular Sensors and Biosensorsmentioning
confidence: 99%
“…In a recent example, Wang and co-workers developed a fluorescent poly(vinyl alcohol) (PVA) hydrogel containing carbon nanodots (CNDs) synthesized from m-phenylenediamine and methacrylic acid for Fe 3+ sensing. 37 While the CNDs alone could emit fluorescence, encapsulation in PVA improved their photostability. Upon their exposure to Fe 3+ , fluorescence quenching was observed due to non-radiative electron transfer from the CNDs to Fe 3+ , following the Stern− Volmer equation linearly from a LOD of 10 μM up to 100 μM.…”
Section: Scheme 1 Analyte Sensing Mechanisms Of Molecular-responsive ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Luminescent hybrid materials, fabricated via covalent conjugation of CQDs to polymers or physical loading of CQDs into polymer matrices, have enriched the application fields of CQDs, which simultaneously shows optical properties of the CQDs and the stimuli-responsiveness and biocompatibility of polymer matrices [ 14 , 15 ]. Ji et al [ 16 ] prepared a high-strength self-healing poly(vinyl alcohol)-carbon nanodots (PVA-CNDs) hydrogel via physical cross-linking of carbon nanodots and poly(vinyl alcohol); this hydrogel can be used as a detector for Fe 3+ once the detection limit reached 10 μM. Huang and coworkers [ 17 ] introduced carbon nanodots (CDs) based on peach gum polysaccharide into a poly(NIPAAm) hydrogel network to fabricate a luminescent hydrogel.…”
Section: Introductionmentioning
confidence: 99%